2019
DOI: 10.1111/pde.13952
|View full text |Cite
|
Sign up to set email alerts
|

Novel KIT mutation presenting as marked lentiginosis

Abstract: Although lentigines are usually benign, they can be associated with a number of genetic syndromes in which neoplasms and other multi‐system pathological processes occur. Here, we report the case of a 6‐year‐old girl who presented with atypical lentiginosis and hyperpigmentation caused by a de novo genetic variant in the KIT gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…T. Takeichi et al reported the c. 2485G > C mutation in exon 17 of KIT in a Japanese pedigree that manifested as progressive hyperpigmentation and lentigines unassociated with any other familiar systemic disease ( 5 ). Almost at the same time, Alain K. et al revealed the same mutation in a 6-year-old girl who presented with atypical lentiginosis and hyperpigmentation without systemic disorders ( 1 ).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…T. Takeichi et al reported the c. 2485G > C mutation in exon 17 of KIT in a Japanese pedigree that manifested as progressive hyperpigmentation and lentigines unassociated with any other familiar systemic disease ( 5 ). Almost at the same time, Alain K. et al revealed the same mutation in a 6-year-old girl who presented with atypical lentiginosis and hyperpigmentation without systemic disorders ( 1 ).…”
Section: Discussionmentioning
confidence: 88%
“…Apart from somatic mutations of KIT in melanomas, germline KIT mutations are reported to be associated with other pigmented disorders, often accompanied by GIST or mastocytosis ( 1 , 2 , 4 7 ). However, two independent groups have recently revealed a new missense mutation of KIT in patients with hyperpigmentation and lentigines without systemic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations